PELATIHAN ANALISIS LAPORAN KEUANGAN BADAN USAHA MILIK DESA (BUM DESA) DI PELALAWAN - Zurman; Safitri, Yulia; Sufanda, Zerry; Helmi, Pebriza (LPPM Universitas Awal Bros, 2023)
BUM Desa is a legal entity established by the village and/or together with villages to manage businesses, utilize assets, develop investment and productivity, provide services, and/or provide other types of businesses for the greatest welfare of the village community. Thus, the government and community's expectation for the growth of the village economy and community welfare is attached to BUM Desa. In Riau Province, all villages in Riau have BUM Desa, totaling 1,591 villages. Pelalawan Regency already have BUM Desa with a total of 104 BUM Desa units. BUM Desa in Pelalawan are actively running with good development as 73 BUM Desa have generated net profit > 100 million. However, BUM Desa has not analyzed financial statements that will be useful in considering BUM Desa's financial decision making. The purpose of this community service activity, namely in the form of training in analyzing the financial statements of Village-Owned Enterprises (BUM Desa) in Pelalawan Regency, is to provide knowledge about financial statements and analysis of BUM Desa financial statements. In order to achieve the above objectives, the implementation of this community service activity has been carried out using several methods, namely as follows, namely pre-test, lecture, dialogue, and post-test. This community service activity was carried out on October 19, 2023 in Pelalawan Regency. The participants in this activity were Operational Executives of BUM Desa, namely 24 Operational Executives from 24 BUM Desa in Pelalawan.